Taxonomic review of the katydid genus Alloteratura (Orthoptera: Tettigoniidae; Meconematinae) with the description of one new species from Thailand - Tan, Ming Kai; Artchawakom, Taksin (Zootaxa, 2017)
Alloteratura Hebard, 1922 is a genus of katydid from the speciose Meconematinae, most easily characterised by maxillary palpi with extremely short apical segment. Currently, two subgenera exists: subgenus Alloteratura Hebard, 1922 (33 species) and Meconemopsis Karny, 1922 (11 species). In this taxonomic review, one new species of the subgenus Meconemopsis from Thailand is described: A. (M.) dawwruengi sp. nov. Illustrated keys to species for both subgenera are also presented here.